2021
DOI: 10.1016/j.ihj.2021.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Guide catheter extension systems: Hype or a need?

Abstract: Guide catheter extension system (GCES) is a valuable tool for interventional cardiologists, especially in complex cases. GCES increases guide back-up support and is crucial in complex PCI procedures, particularly in cases of severe calcification and tortuosity. Apart from their primary use to increase back-up support of guide by providing coaxial alignment, deep intubation and facilitation of stent delivery, GCES are now being increasingly used in different clinical indications including complex and high-risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Globally, at least seven guide extension catheter systems are available, but only three of them are commercially available in India [GuideLiner V3 Catheter (Teleflex, USA), Guidezilla II Guide Extension Catheter (Boston Scientific, USA), and Telescope Guide Extension Cathete] with limited use in small number of centers. [3] In the present study, we used the Guidezilla II Guide Extension Catheter for all the patient, and we reported a 100% procedural success rate. Similarly, a recent study reported 98.7% procedural success rate with the GuideLiner catheter to in 317 complex lesions.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Globally, at least seven guide extension catheter systems are available, but only three of them are commercially available in India [GuideLiner V3 Catheter (Teleflex, USA), Guidezilla II Guide Extension Catheter (Boston Scientific, USA), and Telescope Guide Extension Cathete] with limited use in small number of centers. [3] In the present study, we used the Guidezilla II Guide Extension Catheter for all the patient, and we reported a 100% procedural success rate. Similarly, a recent study reported 98.7% procedural success rate with the GuideLiner catheter to in 317 complex lesions.…”
Section: Discussionmentioning
confidence: 72%
“…Among many causes of procedural failure, failure to deliver equipment (stent/balloon/ thrombosuction device/rotablation catheter/ coils etc.) is frequent [1,3]. Poor back-up force, poor axial alignment (increased friction between stiff stent and vascular wall), and increased tortuosity of the target vessel are the major causes of equipment delivery failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the main indications for GGEC I use are: (1) anomalous origin or angulated take-off of native coronary arteries; (2) extremely tortuous vessel; (3) heavy calcification; (4) distally located lesion; (5) picking up the retrograde wire during CTO intervention; (6) releasing the burr incarceration ( 11 , 30 , 31 ). In the present study, the main indications were heavy calcification (67%) followed by extreme tortuosity (12.2%), extreme tortuosity and heavy calcification (10.9%), distally located lesion (4.5%), picking up the retrograde wire when using the active greeting technique (AGT, 3.2%), anomalous origin of the vessel (1.8%), and to release the burr incarceration (0.4%).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the main indications were heavy calcification (67%) followed by extreme tortuosity (12.2%), extreme tortuosity and heavy calcification (10.9%), distally located lesion (4.5%), picking up the retrograde wire when using the active greeting technique (AGT, 3.2%), anomalous origin of the vessel (1.8%), and to release the burr incarceration (0.4%). In addition, the GGEC I is usually used for remedial purposes, which inevitably leads to longer operation time, higher radiation exposure dose, and higher contrast agent dosage ( 11 , 31 , 32 ). Still, the results of the SYNTAX I score stratification in this study indicate that the SYNTAX score was beneficial in guiding the revascularization strategy, and anatomical characteristics were more significant in the successful treatment of a single target vessel.…”
Section: Discussionmentioning
confidence: 99%